Individual Grain Analysis of the Rare Dioctahedral Mica Celadonite Using Analytical Transmission Electron Microscopy - Lau, Todd R. (My University, 2011)
This project explores the occurrence of a rare dioctahedral micafound along the Cambrian-Precambrian boundary at Big Falls County Park in Eau Claire County, Wisconsin. The goal is to do individual grain quantitative chemical analysis using a high resolution analytical transmission electron microscope (ATEM). This allows quantitative measurement of the composition of individual grains on the nanoscale, without the contamination of non-celadonite grains, which bulk chemical analysis cannot provide.
Color poster with text, tables, maps, graphs, and images.
Keywords: Mica--Wisconsin--Eau Claire County--Analysis; Celadonite--Wisconsin--Eau Claire County--Analysis; Transmission electron microscopy; Posters; Big Falls County Park (Eau Claire, Wis.)